2004
DOI: 10.1093/jaoac/87.2.411
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Aflatoxins, Ochratoxin A, and Zearalenone in Grains by New Immunoaffinity Column/Liquid Chromatography

Abstract: The simultaneous determination of mycotoxins was performed in 3 steps: extraction, cleanup, and detection. For extraction, a mixture of acetonitrile–water (60 + 40, v/v) was proved appropriate. For cleanup, a new Afla-Ochra-Zea immunoaffinity column was used. After derivatization with trifluoroacetic acid, the mycotoxins aflatoxins, ochratoxin A (OTA), and zearalenone (ZEA) were determined simultaneously by liquid chromatography with fluorescence detection. The detection limits in different matrixes after clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(19 citation statements)
references
References 0 publications
1
17
0
1
Order By: Relevance
“…Toxicology program have reviewed hundreds of chemicals, mixtures, and natural products and then graded the cancer risk posed to humans (Abnet 2007). All analytical procedures include 3 steps: extraction, purification (if necessary), and determination (Gobel and Lusky 2004; Ren and others 2007).…”
Section: Mycotoxinsmentioning
confidence: 99%
“…Toxicology program have reviewed hundreds of chemicals, mixtures, and natural products and then graded the cancer risk posed to humans (Abnet 2007). All analytical procedures include 3 steps: extraction, purification (if necessary), and determination (Gobel and Lusky 2004; Ren and others 2007).…”
Section: Mycotoxinsmentioning
confidence: 99%
“…It has been reported that all the AFs have a molar absorptivity of 20,000 cm 2 /mol exhibiting maximum absorption at 360 nm (Akbas & Ozdemir, ). Experimental data suggested that the detection limit of AFs can be improved by the selection of appropriate method for extraction and cleanup procedure (Ali et al, ; Göbel & Lusky, ). The sensitivity of UV system is not enough to detect AFs in trace levels (Alcaide‐Molina et al, ) since its limit of detection reaches up to only micro molar ranges (Couderc, Caussé, & Bayle, ).…”
Section: Detection Techniquesmentioning
confidence: 99%
“…It revealed that the developed method had higher enrichment factor and similar LODs with the listed methods. 12,[33][34][35] Furthermore, the new derivative method has distinct advantages in terms of good sensitivity at the high group selectivity, simplicity of instrumentation, and cost-effectiveness.…”
Section: Analyses Of Real Samplesmentioning
confidence: 99%